2018
DOI: 10.1186/s12872-018-0821-5
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the assessment of endothelial function with peripheral arterial volume

Abstract: BackgroundCurrently, many methodological approaches have been developed to assess peripheral endothelial function. However, a development of the noninvasive and automated technique for routinely assessing endothelial function is still required. We evaluated the potential value of a new method to measure peripheral endothelial function with reactive hyperemia peripheral arterial volume (RH-PAV) in patients with chest pain.MethodsWe used a novel oximeter-like probe to detect the peripheral arterial volume (PAV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Furthermore, PAV was reduced in patients with established CAD, which is consistent with our previous study. 5 As a conventional predictor of the risk of CAD, the AFRS shows a strong positive correlation with the prevalence of significant CAD. 22 In the present study, we adopted the AFRS as the baseline model to assess the probability of CAD before CAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PAV was reduced in patients with established CAD, which is consistent with our previous study. 5 As a conventional predictor of the risk of CAD, the AFRS shows a strong positive correlation with the prevalence of significant CAD. 22 In the present study, we adopted the AFRS as the baseline model to assess the probability of CAD before CAG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, peripheral artery volume (PAV) technology is a newly developed method for quantifying peripheral endothelial function during reactive hyperemia. 5 The basic principle of PAV is the same as that of peripheral arterial tonometry (PAT). PAT technology assesses the arterial pulse wave amplitude of the finger by a pressure sensor, while PAV records pulsatile hemoglobin flow as a surrogate for blood flow volume with a photoplethysmographic finger probe.…”
Section: Introductionmentioning
confidence: 99%
“…32359 "Method for diagnosing endothelium-dependent vasodilatation in children", IPC Measurement of flow-dependent dilatation of the brachial artery according to ultrasound data is currently considered as the «gold standard» for the endothelial function of vessels study [4,17,18,20]. The study method is high-tech and non-invasive, which greatly simplifies and accelerates the diagnosis of ED in children with various pathology [2,11,17,19]. Endothelium-dependent vasodilatation (EDVD) test was performed as follows: patients were examined in the supine position after a 10-15-minute rest, at least a 10-hour fast and abstention from coffee, tea, bad habits and exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Daoyuan's team examined 93 people (53 with coronary heart disease) and concluded that PAV may provide as accurate results as FMD, while being easier to perform. Moreover, the authors indicated that PAV has the potential to become a non-invasive method of early identification of patients at high risk of coronary artery disease [47].…”
Section: Endothelial Function Assessmentmentioning
confidence: 99%